Análisis comparativo de los estados financieros en la Farmacia Tu Ahorro de la ciudad de Babahoyo en el periodo contable 2021-2022 - Sarmiento Méndez, Madelen Joselynda (2023)
Tu Ahorro Pharmacy is a company dedicated to the sale of medicines and health-related products. Currently, companies tend to have problems controlling their costs of sales and operational expenses, and may be incurring unnecessary costs due to poor planning and control. If companies do not correct these deficiencies, they could face difficulties in making informed decisions in critical areas and obtaining adequate financing from investors. The case study focuses on the importance of comparative analysis of the financial statements of Tu Ahorro Pharmacy in the accounting period 2021-2022. Comparative analysis of financial statements is a fundamental tool for evaluating the financial situation and performance of the company, identifying trends and patterns, and making informed and strategic decisions. This research employed a mixed research approach, meaning that quantitative and qualitative elements were combined in data collection and analysis. The accounts that make up the income statement described in detail to obtain quantitative information on the company's financial situation, and various tools were used to gain a deeper understanding of the relevant topics for the study.